PENGEMBANGAN MODEL PEMBELAJARAN INVESTIGASI KELOMPOK PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL UNTUK MENINGKATKAN KEPEKAAN SOSIAL SISWA (Penelitian dan Pengembangan pada Siswa SMP se- Kabupaten Garut) - lutfi asyari (Journal Civics and Social Studies, 2020)
ABSTRACTLutfi Asy’ari . The Development of Group Investigation Instuctional Model  in Social Science to Improve  Students’ Social Sensitivity (A Research and Development in  Junior Hight School in Garut).This  research wich aims   to produce  an instructional  group investigation model for Social Science to improve Students’ Social Sensitivity. To achieve this goal, this  research was conducted  using  research and development (R &D) methods . The research subjects were the sosial science teachers and eighth grade students 12 Junior Hight Schools at 12 sub-districts in Garut Regency. The instruments used to gain data were questionary, observation, document, interview and attitude scale. Data were analized by using Pearsons Product Moment Correlation, Cronbach’s Alpha (α) , Kolmogorov Smirnov Test, Lavene test, t-test, Wilcoxon test, and Mann-Whitney test. The result of validity test indicated the the score gain of experimental group is higher than that of the control group in junior high schools that were categorized as excellent, good and averege. The findings led to the conclusion that Group investigation instructional Model was determined as model of effective development result to improve students social sensitivity. This result was supported by  some factors: (a) design model that gave a clear overview related to learning scenario, (b) the learning implementation on the basis of group dynamics, and (c) more priority on attitude based evaluation. Keywords: insructional, group investigation, studens’ social sensitivity